Metabolomic Profiling Reveals Cellular Reprogramming of B-Cell Lymphoma by a Lysine Deacetylase Inhibitor through the Choline Pathway - Pera, Benet; Krumsiek, Jan; Assouline, Sarit E.; Marullo, Rossella; Patel, Jayeshkumar; Phillip, Jude M.; Román, Lidia; Mann, Koren K.; Cerchietti, Leandro (EBioMedicine, 2018)
Despite the proven clinical antineoplastic activity of histone deacetylase inhibitors (HDACI), their effect has been reported to be lower than expected in B-cell lymphomas. Traditionally considered as “epigenetic drugs”, HDACI modify the acetylation status of an extensive proteome, acting as general lysine deacetylase inhibitors (KDACI), and thus potentially impacting various branches of cellular metabolism. Here, we demonstrate through metabolomic profiling of patient plasma and cell lines that the KDACI panobinostat alters lipid metabolism and downstream survival signaling in diffuse large B-cell lymphomas (DLBCL). Specifically, panobinostat induces metabolic adaptations resulting in newly acquired dependency on the choline pathway and activation of PI3K signaling. This metabolic reprogramming decreased the antineoplastic effect of panobinostat. Conversely, inhibition of these metabolic adaptations resulted in superior anti-lymphoma effect as demonstrated by the combination of panobinostat with a choline pathway inhibitor. In conclusion, our study demonstrates the power of metabolomics in identifying unknown effects of KDACI, and emphasizes the need for a better understanding of these drugs in order to achieve successful clinical implementation. •Lysine deacetylase inhibitor (KDACI) treatment alters choline metabolism in B-cell lymphoma patients.•KDACI-treated lymphoma cells acquire PI3K pathway dependency via increased choline kinase A (CHKA) activity.•Targeting the acquired choline dependency improves the anti-lymphoma effect of KDACI. Pera et al. explored the effects of the lysine deacetylase inhibitor panobinostat in the metabolism of patients with lymphoma. They demonstrated that panobinostat alters choline metabolism leading to PI3K pathway activation. Their findings revealed the mechanism behind the anti-lymphoma activity of dual lysine deacetylase/PI3K inhibitors, and uncovered a novel therapeutic strategy based on targeting choline pathway following panobinostat treatment.